The essence and the principles of the creation of the strategy of blue ocean - Belova, Tatyana; Glushanitsya, Anastasia; Krainiuchenko (Fornolyak), Olga (My University, 2015)
There were considered the essences and the differences of the concepts of the “Red Ocean” and “Blue Ocean”. It was disclosed the content and the main features of the strategy of the blue ocean. The main principles of the blue ocean strategy were formulated, too. And there are examples of the most successful companies which created their blue ocean.
Keywords: red ocean; blue ocean; market niche; blue ocean strategy; червоний океан; блакитний океан; ринкова ніша; стратегія блакитного океану; красный океан; голубой океан; рыночная ниша; стратегия голубого океана; кафедра маркетингу